2007
DOI: 10.1002/mus.20816
|View full text |Cite
|
Sign up to set email alerts
|

Children are more susceptible to central fatigue than adults

Abstract: Performance in high-intensity exercise is dependent on the ability to activate motor units. The main aim of this study was to test the hypothesis that adult men and women (age 19-27 years) are able to maintain higher levels of voluntary activation (VA) in knee extensor muscles than boys and girls (age 12-14 years). The volunteers (n = 7 in each group) performed three 5-s maximal voluntary contractions (MVCs) and a continuous 2-min MVC. The VA and fatigue of the muscles was assessed by applying 250-ms 100-HZ te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
74
2
7

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(93 citation statements)
references
References 30 publications
10
74
2
7
Order By: Relevance
“…However, in adults, any exercise at a short muscle length reduces the development of peripheral fatigue [35] and promotes the development of central fatigue [36]. Should these effects hold true in children, this could explain, at least in part, the results of studies reporting a lower peripheral fatigue and a greater central fatigue in prepubertal children and adolescents compared to adults [37,38]. However, the effect of muscle length on the development and etiology of neuromuscular fatigue should be confirmed in children and adolescents and a systematic comparison at the optimal angle should be considered when the effects of fatigue protocols are compared between children, adolescents and adults.…”
Section: Musculo-tendinous Stiffnessmentioning
confidence: 99%
“…However, in adults, any exercise at a short muscle length reduces the development of peripheral fatigue [35] and promotes the development of central fatigue [36]. Should these effects hold true in children, this could explain, at least in part, the results of studies reporting a lower peripheral fatigue and a greater central fatigue in prepubertal children and adolescents compared to adults [37,38]. However, the effect of muscle length on the development and etiology of neuromuscular fatigue should be confirmed in children and adolescents and a systematic comparison at the optimal angle should be considered when the effects of fatigue protocols are compared between children, adolescents and adults.…”
Section: Musculo-tendinous Stiffnessmentioning
confidence: 99%
“…children have demonstrated a lower degree of central fatigue than adults during maximal isokinetic and isometric contractions [8,17]. On the other hand, children showed a greater reduction in the level of voluntary activation, as well as a smaller decrease in peripheral force generation capacity during a 2-min maximal isometric knee extension effort [18]. Hence, the available results are controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Although not all studies have demonstrated a lower motor-unit activation in children (Streckis et al 2007), Halin et al (2002) proposed that children's neuromuscular system may be more adaptive to a training stimulus, compared with that of adults.…”
Section: Introductionmentioning
confidence: 99%